1208. Development of a Novel Synthetic Glycan to Prevent Bacterial Infections and Ameliorate Respiratory Viral Infections. (31st December 2020) - Meisner, Jeffrey; Lee, Jackson; Lawrence, Jonathan; Roed, Megan; Vlieg, Johan van Hylckama
Abstract: Background: The prevention and treatment of bacterial infections is a human health challenge. A disadvantage of antibiotics is that they often kill beneficial commensal, bacteria in addition to, pathogenic bacteria. Indiscriminate killing disrupts the homeostasis between commensal bacteria and the host gut epithelium allowing colonization of the gut by pathogenic bacteria and increases susceptibility to infections. This research was done to develop a non-antibiotic modality to prevent bacterial infections by growing, rather than killing, commensal bacteria in the gut. Gut commensal bacteria grown on carbohydrates produce short-chain fatty acids (SCFAs) that support gut homeostasis maintenance and promote resistance to bacterial colonization. SCFAs have direct and indirect effects on the gut and lung mucosal immune system. They have also been linked to respiratory viral infection reduction and shown to influence macrophage function to mitigate pro-inflammatory neutrophil-mediated tissue damage. Methods: A library of over 1, 500 synthetic proprietary glycans, termed Microbiome Metabolic Therapies (MMT™), was synthesized using different chemical and enzymatic approaches. An ex vivo platform using fecal bacterial communities from human subjects was devised to screen MMTs for their abilities to deplete pathogenic bacteria, and modulate multiple aspects of bacterial metabolism. Results: KB109 was identified based on its ability to reduce the relative abundance of a diversity of pathogens including clinically relevant Gram-negative and Gram-positive bacteria in human fecal communities. KB109 also increased the relative abundance of prevalent commensal bacteria. Monoculture experiments demonstrated that KB109 promotes the growth of commensal bacteria, but not pathogens. Ex vivo screening revealed that KB109 consistently increased SFCA production across multiple fecal communities. Conclusion: KB109 represents an appealing activity profile and offers an opportunity to prevent enteric and systemic bacterial infections by promoting gut homeostasis and colonization resistance, and ameliorating respiratory viral infections by stimulating immune homeostasis. KB109 is under evaluation in two COVID-19 clinical studies. Disclosures: Jeffrey Meisner, PhD, Kaleido Biosciences (Employee, Shareholder) Jackson Lee, PhD, Kaleido Biosciences (Employee, Shareholder) Jonathan Lawrence, PhD, Kaleido Biosciences (Employee, Shareholder) Megan Roed, BA, Kaleido Biosciences (Employee, Shareholder) Johan van Hylckama Vlieg, PhD, Kaleido Biosciences (Employee, Shareholder)